Some general traits of the e-cash system and a review of a compact e-cash scheme with practical and complete tracing - Popovska Mitrovikj, Aleksandra; Stamenkovska, Ema; Dimitrova, Vesna (Scientific Technical Union of Mechanical Engineering" Industry 4.0", 2020)
The e-cash methodology has its advantages compared to other payment systems and it has brought big changes to the way business is being conducted. Money becomes an intangible item and travels electronically across the world in a widely open network that might expose it to risks. This means that secure end-to-end connections are needed and many different cryptographic algorithms are used to achieve it. In this paper we will go through the main metrics that characterize them and the main properties of the e-cash system. Finally, a review of a compact e-cash scheme with practical and complete tracing will be given.
Keywords: COMPACT E-CASH, CIA TRIAD, E-CASH PROPERTIES, PAYMENT SCHEME